PENGARUH PEMBERIAN AGEN HAYATI DAN DOSIS PUPUK NPK TERHADAP PERTUMBUHAN DAN PRODUKSI BAWANG MERAH - Madila, Mutiara Hersa; Syam, Netty; Alimuddin, Suraedah; Abdullah, Abdullah (Percetakan Umi Toaha Makassar, 2025)
Enrekang Regency is the largest shallot producer in South Sulawesi; however, its production increase still depends on land expansion. Moreover, continuous use of inorganic fertilizers triggers the development of pathogenic microbes that damage the plants. Therefore, a combination of biological agents and low-dose NPK fertilizer is needed to suppress soil pathogenic microbes and improve productivity. This study aims to analyze the effect of biological agents on the growth and production of shallots, assess the effect of NPK fertilizer dosage on shallot growth and production, and analyze the interaction between biological agents and NPK fertilizer in the context of shallot growth and production. The research was conducted in Saruran Village, Anggeraja District, Enrekang Regency, from August to October 2025. The experimental design used was a randomized block design with two factors. The first factor was Trichoderma and mycorrhiza with four levels: control, Trichoderma 20 g/ plant, mycorrhiza 20 g/ plant, and a combination of Trichoderma 10 g /plant and mycorrhiza 10 g/ plant. The second factor was NPK fertilizer dosage with four levels: control, 50 g/plot, 37.5 g/plot, and 25 g/plot. Thus, 16 treatment combinations were obtained, each repeated three times, resulting in a total of 48 experimental units. The research parameters included plant height, number of leaves, bulb weight per clump, number of bulbs per clump, and bulb weight per plot. The results showed that the application of the biological agents Trichoderma + mycorrhiza had a positive effect on the number of leaves (23.67 leaves), bulb weight per clump (74.67 g), and fresh and dry bulb weight per plot (935.75 g and 357.28 g, respectively). The application of NPK fertilizer at 50.0 g/ plant positively affected plant height (28.55 cm) and the number of bulbs (6.75 bulbs). The combination of both treatments significantly influenced plant height (30.67 cm) and bulb weight per clump (81.33 g).